The Role of Teachers in Developing Student Character Amidst the Digitalization of Education - Deviana Mayasyifa; Iim Siti Karimah; Citera Yusrina (CV. Ksatria Siliwangi, 2026)
The current digitalization sweeping the world of education presents a paradox in which easy access to information often contradicts the development of students' character. This article aims to critically examine the dynamics of teachers' roles in developing students' character amidst the onslaught of an instant and permissive digital culture. This research employs a library research method with an interpretive qualitative approach, analyzing various scientific literature and the latest research findings from the past decade. The study's findings indicate that excessive screen time has triggered a degradation of social empathy and increased students' vulnerability to immoral behavior in cyberspace, such as cyberbullying. Further analysis reveals that artificial intelligence technology can indeed replace teachers as conveyors of factual information, but it will never be able to replace their role as moral facilitators and ethical role models. Therefore, it is necessary to transform the role of teachers into value curators capable of integrating digital literacy with local wisdom through a humanistic pedagogical approach. The article's conclusion emphasizes that the synergy between technological adaptability and teachers' personal integrity is key to saving the next generation from an identity crisis in the era of information disruption.